(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The methodology employed in this research was designed to identify and characterize the infectious bursal disease virus (IBDV) at the molecular level, originating from recent outbreaks in Bangladesh. Materials and Methods: The IBDV outbreak farm was investigated, and bursa of fabricius (BF) specimens were acquired from infected chickens. Initially, viruses in the processed samples were detected in chicken embryo fibroblast (CEF) cells, and the RT-PCR method was used to confirm IBDV. The positive samples were injected through chorioallantoic membrane route into the embryo of a 10-day-old specific pathogen-free (SPF) egg for virus isolation and pathogenicity testing. Finally, we sequenced the VP2 gene to identify phylogenetic relationships and detect mutations. Results: From the 77 collected samples, 42.85% (33/77) were found positive for cytopathic effects in CEF cells, and IBDV was detected in 31.16% (24/77) of the samples by RT-PCR. IBDV was isolated in SPF chicken embryos. In the pathogenicity test, infectious bursal disease was evident in seronegative chickens with visible signs of disease. Sequence analysis shows that the broiler-isolated viruses clustered with genotype A3B2 and backyard chickens with genotype A1B1. The presence of amino acid motifs for virulence markers was revealed in the partially sequenced VP2 gene with a mutation at S254G in four IBDV isolates from broilers. However, amino acids for virulence markers were absent in two isolates from backyard chickens, which shows sequence homology with IBDV classic strains. Conclusion: In this study, we identified and characterized circulating reassorted IBDV from vaccinated broilers, which may be one of the major causes of vaccination failure in broilers. J. Adv. Vet. Anim. Res., 11(3): 534–543, September 2024 http://doi.org/10.5455/javar.2024.k803